Osteoperiosteal Cylindrical Iliac Bone Graft and Minced Cartilage as an Osteochondral Autograft for a Large Osteochondral Lesion - Murat Bozkurt, M.D., Ph.D.; Daria Nayda, M.D.; Ali Şahin, M.D.; Kadir Yavaşoğlı, M.D.; Enejd Veizi, M.D. (Arthroscopy Techniques)
Mosaicplasty is a relatively challenging procedure used in the management of focal osteochondral lesions of the joints. Donor-site morbidity is still the main concern after mosaicplasty because it entails the harvesting of an osteochondral autograft from an otherwise healthy region to be impacted later on the weight-bearing damaged site. We describe a possible alternative to conventional mosaicplasty with subchondral bone support harvested from the iliac crest as an osteoperiosteal autograft and covered with a minced cartilage layer.